Field guide to the birds of the United States and Canada - Floyd, Ted, 1968- (National Geographic, 2025)
"Birders of all ages and stages will appreciate this fully revised and updated edition of National Geographic's field guide, a trusted resource for more than 40 years. Combining a tried-and-true structure with innovations and improvements, this volume belongs on the bookshelf or in the backpack of every enthusiastic bird lover. You'll find: All 1,155 species of the United States and Canada, taxonomically arranged; Fresh new text on each species' appearance, behavior, and habitat, organized for quick reference; More than 70 species and subspecies of Hawaiian birds, new in this edition; Special lists of 199 rare and 40 extinct species; 6/5 range maps based on eBird data from the Cornell Lab of Ornithology, reviewed by experts; Custom illustrations of all species, including key details and plumage variations, annotated to aid identification; Thumb tabs and a visual index inside front and back covers, designed for easy navigation. Authoritative, comprehensive, and fully updated, National Geographic's best-selling bird field guide will satisfy birders young and old, for use in the field or at home."--Back cover.